Chromium-based bimetallic sulfide-porous carbon composite material as well as preparation method and application thereof

By preparing chromium-based bimetal sulfide-porous carbon composites, the problem of insufficient cyclic stability and rate performance of existing bimetal sulfide materials in lithium-ion batteries is solved, and higher specific capacity and better cycle stability and rate performance are achieved.

CN119569118APending Publication Date: 2025-03-07LINGNAN NORMAL UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411753261.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The cycle stability and rate performance of existing bimetallic sulfide materials in lithium-ion batteries are insufficient, making it difficult to meet the high energy density and long life requirements of lithium-ion batteries.

Method used

Using chromium-based bimetallic sulfide-porous carbon composite material, the composite material with lyophilized by a mixed solution of sodium gluconate, metal salt, sulfur source and pore-forming agent was prepared by heat treatment and vulcanizing in an inert atmosphere to prepare a composite material with chromium zinc or chromium manganese sulfide nanoparticles highly dispersed in the carbon network.

Benefits of technology

The specific capacity and cycle stability of the composite material are improved, the volume expansion effect during charging and discharging is alleviated, and the conductivity is enhanced, thereby improving the rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005165528170000011
    Figure HDA0005165528170000011
  • Figure HDA0005165528170000012
    Figure HDA0005165528170000012
  • Figure HDA0005165528170000013
    Figure HDA0005165528170000013
Patent Text Reader

Abstract

The invention belongs to the technical field of micro-nano composite materials, and particularly relates to a chromium-based bimetallic sulfide-porous carbon composite material and a preparation method and application thereof. The preparation method of the chromium-based bimetallic sulfide-porous carbon composite material provided by the invention comprises the following steps: mixing chromium salt and zinc salt, or chromium salt and manganese salt with a sulfur source, sodium gluconate and a pore-forming agent, and preparing the composite material through heat treatment and vulcanization technologies. The chromium-zinc or chromium-manganese bimetallic sulfide-porous carbon composite material prepared by the preparation method has good structural stability and conductivity, and the cycling stability of a battery can be remarkably improved when the chromium-zinc or chromium-manganese bimetallic sulfide-porous carbon composite material is used as a battery material. The prepared chromium-based bimetallic sulfide-porous carbon composite material has important application value in the field of lithium ion battery electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of micro-nano composite materials, and more specifically, relates to a chromium-based bimetallic sulfide-porous carbon composite material and a preparation method and application thereof. Background Art

[0002] In recent years, due to the depletion of fossil fuels and the growth of energy demand, the demand for research on new energy storage technologies has risen sharply. Lithium-ion batteries (LIBs) have the advantages of high energy density, high operating voltage (3.7-3.8V), good cycle performance, and environmental friendliness. They are widely used in various portable electric devices. Among them, the electrode materials of lithium-ion batteries, especially the negative electrode materials, play a pivotal role in the energy density, rate performance and long-term service life of the battery. Therefore, finding a battery negative electrode material with better performance is one of the key points in the development and progress of lithium-ion batteries.

[0003] Monometallic sulfides have a high theoretical specific capacity and are a very promising negative electrode material for lithium-ion batteries. However, in practical applications, monometallic sulfide nanoparticles are prone to agglomeration or accumulation due to their high surface energy, which greatly reduces their available active specific surface area and reduces their specific capacity. In addition, monometallic sulfides such as chromium trisulfide, zinc sulfide and manganese sulfide have poor electrical conductivity. When chromium trisulfide, zinc sulfide and manganese sulfide are used as negative electrode materials for batteries, long-term charging and discharging can easily lead to battery volume expansion and pulverization of electrode materials, resulting in poor cycle capacity and rate capability. Compared with monometallic sulfides, bimetallic sulfides have more redox electron pairs and can provide a higher theoretical lithium storage capacity. Moreover, when one of the metal sulfide components is storing and releasing lithium, the other metal sulfide can act as an inert phase, effectively alleviating the volume expansion effect of the metal sulfide during storage and release of lithium, thereby improving the material's cycle stability.

[0004] However, not all bimetallic combinations have an improvement effect on battery performance. For example, Sharma et al. synthesized FeCo2O4 and MgCo2O4 by decomposing urea and oxalic acid, and the performance of the battery was improved at 60 mA g -1 Under these conditions, the initial specific capacity of FeCo2O4 is 827 mAh g -1 The initial specific capacity of MgCo2O4 is 736 mAh g -1; After 50 cycles, FeCo2O4 has a good capacity retention rate, while MgCo2O4 has a very poor capacity retention rate; This result shows that Fe as a composite element of Co is better than Mg (Yogesh Sharma, N. Sharma, GV Subba Rao, BVR Chowdari. Studies on spinel cobaltites, FeCo2O4 and MgCo2O4 as anodes for Li-ion batteries [J]. Solid State Ionics, 2008, Vol. 179 (15): 587-597). Therefore, how to explore bimetallic sulfides with excellent cycle stability and rate performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a method for preparing a chromium-based bimetallic sulfide-porous carbon composite material.

[0006] The purpose of the present invention is to provide a chromium-based bimetallic sulfide-porous carbon composite material.

[0007] Another object of the present invention is to provide an application of the chromium-based bimetallic sulfide-porous carbon composite material.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention provides a method for preparing a chromium-based bimetallic sulfide-porous carbon composite material, comprising the following steps:

[0010] S1. Sodium gluconate, metal salt, sulfur source and pore-forming agent are mixed and dissolved to obtain a mixed solution, and freeze-dried to obtain a mixed dry powder;

[0011] S2. The dry powder of the mixture prepared in S1 is heat treated and sulfurized at 700 to 900° C. in an inert atmosphere, and the pore-forming agent is removed by post-treatment to obtain a chromium-based bimetallic sulfide-porous carbon composite material;

[0012] Wherein, the metal salt is a chromium salt and a zinc salt; or a chromium salt and a manganese salt.

[0013] The chromium-based bimetallic sulfide-porous carbon composite material provided by the present invention is prepared by freeze-drying combined with heat treatment and vulcanization technology, using sodium gluconate as a chelating agent and a carbon source, and introducing a specific type of metal salt, a sulfur source and a pore-forming agent at the same time. Sodium gluconate is a strong chelating agent that can form a relatively stable chelate with metal ions, which is conducive to the subsequent formation of a uniform and tightly combined composite material. The present invention dissolves and mixes sodium gluconate with a metal salt, a sulfur source and a pore-forming agent, and then forms a layer of a mixture containing a chelate and a sulfur source on the surface of the pore-forming agent microcrystal by freeze drying. In the subsequent heat treatment, the chelate undergoes thermal cracking, and the organic matter therein is carbonized to form a carbon sheet, and the metal ions react with the hydrogen sulfide released by the decomposition of the sulfur source, and the chromium-based bimetallic sulfide Cr2ZnS4 or Cr2MnS4 is generated in situ and loaded on the carbon sheet, and then the pore-forming agent is removed to form holes, and finally a chromium-zinc bimetallic sulfide-porous carbon composite material or a chromium-manganese bimetallic sulfide-porous carbon composite material is obtained.

[0014] In the chromium-based bimetallic sulfide-porous carbon composite material of the present invention, the chromium-zinc sulfide nanoparticles or chromium-manganese sulfide nanoparticles are highly dispersed in the carbon network, avoiding the agglomeration and accumulation phenomenon, and can expose more active sites; at the same time, a synergistic effect is formed between the two metal sulfide components, which is conducive to improving the specific capacity of the composite material. The chromium-zinc or chromium-manganese sulfide nanoparticles are confined by the carbon material, which can effectively alleviate the volume expansion effect during charging and discharging, which is conducive to enhancing the cycle stability of the composite material; and the chromium-zinc or chromium-manganese sulfide nanoparticles are closely combined with the conductive carbon material to improve the overall conductivity of the composite material, which is conducive to improving the rate performance of the composite material.

[0015] Preferably, the molar concentration of sodium gluconate in the mixed solution is 0.01 to 3.0 mol·L -1 More preferably, the molar concentration of sodium gluconate in the mixed solution is 0.1 to 1 mol·L -1 More preferably, the molar concentration of sodium gluconate in the mixed solution is 0.1 to 0.2 mol·L -1 .

[0016] Preferably, the molar ratio of the metal ion of the metal salt, sodium gluconate, sulfur source and pore-forming agent in the mixed solution is 1:1-6:5-10:50-200. Preferably, the molar ratio of the metal ion, sodium gluconate, sulfur source and pore-forming agent in the mixed solution is 1:3-5.5:5-8.5:100-155.

[0017] Preferably, in the chromium salt and the zinc salt, the molar ratio of chromium ion to zinc ion is 1 to 3:1;

[0018] Alternatively, the molar ratio of chromium ion to manganese ion in the chromium salt and the manganese salt is 1 to 3:1.

[0019] Preferably, the chromium salt is one or more of chromium chloride, chromium sulfate or chromium nitrate.

[0020] Preferably, the zinc salt is one or more of zinc nitrate, zinc acetate or zinc sulfate; or, the manganese salt is one or more of manganese chloride, manganese acetate or manganese sulfate.

[0021] Preferably, the sulfur source is one or both of thiourea or thioacetamide.

[0022] Preferably, the heat treatment and vulcanization time is 1 to 4 hours.

[0023] Preferably, the pore-forming agent is selected from one or both of sodium chloride and potassium chloride.

[0024] Preferably, the post-treatment method for removing the pore-forming agent is: water washing and freeze drying.

[0025] Furthermore, the present invention protects the chromium-based bimetallic sulfide-porous carbon composite material prepared by the preparation method.

[0026] In addition, the present invention also protects the use of the chromium-based bimetallic sulfide-porous carbon composite material in lithium-ion batteries.

[0027] The chromium-based bimetallic sulfide-porous carbon composite material of the present invention can be used as a negative electrode material of a battery to prepare a lithium-ion battery. The inventors have found that the lithium-ion battery prepared using the composite material of the present invention can significantly improve the specific capacity stability during multiple charge and discharge processes.

[0028] The present invention has the following beneficial effects:

[0029] (1) The present invention provides a method for preparing a chromium-based bimetallic sulfide-porous carbon composite material. In the chromium-based bimetallic sulfide-porous carbon composite material prepared by the preparation method, chromium-zinc sulfide nanoparticles or chromium-manganese sulfide nanoparticles are highly dispersed in the carbon network, avoiding the agglomeration and accumulation of metal nanoparticles and exposing more active sites; at the same time, a synergistic effect is formed between the two metal sulfide components, which is beneficial to improving the specific capacity of the composite material. The chromium-zinc or chromium-manganese sulfide nanoparticles are confined by the carbon material, which can effectively alleviate the volume expansion effect during charging and discharging, which is beneficial to enhancing the cycle stability of the composite material; and the chromium-zinc or chromium-manganese sulfide nanoparticles are closely combined with the conductive carbon material to improve the overall conductivity of the composite material, which is beneficial to improving the rate performance of the composite material.

[0030] (2) The preparation method of the present invention is simple, low-cost, can be quickly synthesized in large quantities, and has the advantages of high product yield. In addition, the prepared composite nanomaterial has uniform morphology. Using it as a battery material can significantly improve the cycle stability of the battery. The chromium-based bimetallic sulfide-porous carbon composite material prepared by the present invention has important application value in the field of lithium-ion battery electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the XRD pattern of chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) prepared in Example 1.

[0032] Figure 2 This is a scanning electron microscope image of the chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) prepared in Example 1.

[0033] Figure 3 This is a scanning electron microscope image of chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) prepared in Example 2.

[0034] Figure 4 This is the XRD pattern of chromium manganese sulfide-porous carbon (Cr2MnS4-PC) prepared in Example 3.

[0035] Figure 5 This is a scanning electron microscope image of chromium manganese sulfide-porous carbon (Cr2MnS4-PC) prepared in Example 3.

[0036] Figure 6 This is a scanning electron microscope image of chromium manganese sulfide-porous carbon (Cr2MnS4-PC) prepared in Example 4.

[0037] Figure 7 This is a scanning electron microscope image of the chromium zinc sulfide (Cr2ZnS4) prepared in Comparative Example 1.

[0038] Figure 8 This is a scanning electron microscope image of chromium manganese sulfide (Cr2MnS4) prepared in Comparative Example 2.

[0039] Fig. 9 This is the XRD pattern of chromium trisulfide-porous carbon (Cr2S3-PC) prepared in Comparative Example 3.

[0040] Fig.10 This is a scanning electron microscope image of chromium trisulfide-porous carbon (Cr2S3-PC) prepared in Comparative Example 3.

[0041] Fig.11 This is the XRD pattern of zinc sulfide-porous carbon (ZnS-PC) prepared in Comparative Example 3.

[0042] Fig.12This is a scanning electron microscope image of zinc sulfide-porous carbon (ZnS-PC) prepared in Comparative Example 3.

[0043] Fig.13 This is the XRD pattern of the mixture of chromium trisulfide, titanium oxide and sulfide, and carbon material prepared in Comparative Example 4.

[0044] Fig.14 This is the XRD pattern of the mixture of chromium trisulfide, niobium oxide and sulfide and carbon material prepared in Comparative Example 5.

[0045] Fig.15 The chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) prepared in Example 1 is 0.1A·g -1 Cycling performance diagram at current density of .

[0046] Fig.16 The chromium manganese sulfide-porous carbon (Cr2MnS4-PC) prepared in Example 3 is 0.1A·g -1 Cycling performance diagram at current density of .

[0047] Fig.17 The chromium zinc sulfide (Cr2ZnS4) prepared in Comparative Example 1 was 0.1A·g -1 Cycling performance diagram at current density of .

[0048] Fig.18 The chromium manganese sulfide (Cr2MnS4) prepared in Comparative Example 2 was 0.1A·g -1 Cycling performance diagram at current density of .

[0049] Fig.19 The chromium trisulfide-porous carbon and zinc sulfide-porous carbon mixtures prepared in Comparative Example 3 were -1 Cycling performance diagram at current density of .

[0050] Fig. 20 This is a cycle performance diagram of a mixture of chromium trisulfide, titanium oxide and sulfide, and carbon material prepared in Comparative Example 4 at a current density of 0.1 A g-1.

[0051] Fig.21 The mixture of chromium trisulfide, niobium oxide and sulfide and carbon material prepared in Comparative Example 5 was heated to 0.1A·g -1 Cycling performance diagram at current density of . DETAILED DESCRIPTION

[0052] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0053] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0054] Example 1

[0055] S1. Dissolve 3mmol of sodium gluconate in 30mL of deionized water and stir until completely dissolved; then add 0.66mmol of chromium chloride, 0.33mmol of zinc sulfate, 5mmol of thiourea and 100mmol of sodium chloride in sequence and stir until completely dissolved;

[0056] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0057] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750°C in an inert atmosphere (nitrogen) for 2 hours. The obtained product is repeatedly washed with water to remove sodium chloride, and then freeze-dried to obtain the final chromium zinc sulfide-porous carbon composite material (Cr2ZnS4-PC).

[0058] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS16-0507) of cubic phase Cr2ZnS4. Figure 1 The scanning electron microscope image is shown in Figure 2 , showing that the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology, and its surface structure is distributed with many chromium zinc sulfide nanoparticles.

[0059] Example 2

[0060] S1. Dissolve 5 mmol of sodium gluconate in 30 mL of deionized water under stirring and stir until completely dissolved; then add 0.66 mmol of chromium chloride, 0.33 mmol of zinc sulfate, 8 mmol of thiourea and 150 mmol of sodium chloride in sequence and stir until completely dissolved;

[0061] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0062] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 850°C in an inert atmosphere (nitrogen) for 3 hours. The obtained product is repeatedly washed with water 3 times to remove sodium chloride, and then freeze-dried to obtain the final chromium zinc sulfide-porous carbon composite material (Cr2ZnS4-PC).

[0063] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS16-0507) of cubic crystal phase Cr2ZnS4. Figure 3 , showing that the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology.

[0064] Example 3

[0065] S1. Dissolve 3mmol of sodium gluconate in 30mL of deionized water and stir until completely dissolved; then add 0.66mmol of chromium chloride, 0.33mmol of manganese chloride, 5mmol of thiourea and 100mmol of sodium chloride in sequence and stir until completely dissolved;

[0066] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0067] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750°C in an inert atmosphere (nitrogen) for 2 hours. The obtained product is repeatedly washed with water to remove sodium chloride, and then freeze-dried to obtain the final chromium manganese sulfide-porous carbon composite material (Cr2MnS4-PC).

[0068] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS 36-1441) of cubic phase Cr2MnS4. Figure 4 The scanning electron microscope image is shown in Figure 5 , showing that the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology, and its surface structure is distributed with many chromium manganese sulfide nanoparticles.

[0069] Example 4

[0070] S1. Dissolve 5 mmol of sodium gluconate in 30 mL of deionized water under stirring and stir until completely dissolved; then add 0.66 mmol of chromium chloride, 0.33 mmol of manganese chloride, 8 mmol of thiourea and 150 mmol of sodium chloride in sequence and stir until completely dissolved;

[0071] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0072] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 850°C in an inert atmosphere (nitrogen) for 3 hours. The obtained product is repeatedly washed with water 3 times to remove sodium chloride, and then freeze-dried to obtain the final chromium manganese sulfide-porous carbon composite material (Cr2MnS4-PC).

[0073] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS 36-1441) of cubic crystal phase Cr2MnS4. Figure 6 , showing that the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology.

[0074] Comparative Example 1

[0075] S1. Dissolve 0.66mmol chromium chloride, 0.33mmol zinc sulfate, and 5mmol thiourea in 30mL water under stirring and stir until completely dissolved;

[0076] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0077] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750°C for 2 hours in an inert atmosphere (nitrogen). The obtained product is repeatedly washed with water 3 times, and then freeze-dried to obtain the final chromium zinc sulfide material.

[0078] The difference between this comparative example and Example 1 is that sodium gluconate (chelating agent and carbon source) and sodium chloride (pore-forming agent) are not added in step S1.

[0079] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS16-0507) of cubic crystal phase Cr2ZnS4. Figure 7 , showing that the product is irregular nanoparticles agglomerated together.

[0080] Comparative Example 2

[0081] S1. Dissolve 0.66mmol chromium chloride, 0.33mmol manganese chloride, and 5mmol thiourea in 30mL water under stirring and stir until completely dissolved;

[0082] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0083] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750°C for 2 hours in an inert atmosphere (nitrogen). The obtained product is repeatedly washed with water 3 times, and then freeze-dried to obtain the final chromium manganese sulfide material.

[0084] The difference between this comparative example and Example 3 is that sodium gluconate (chelating agent and carbon source) and sodium chloride (pore-forming agent) are not added in step S1.

[0085] The product has been tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS 36-1441) of cubic crystal phase Cr2MnS4. Figure 8, showing that the product is irregular nanoparticles agglomerated together.

[0086] Comparative Example 3

[0087] S1. Dissolve 2 mmol of sodium gluconate in 30 mL of deionized water and stir until completely dissolved; then add 0.66 mmol of chromium chloride, 4 mmol of thiourea and 70 mmol of sodium chloride in sequence and stir until completely dissolved;

[0088] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0089] S3. The dry powder was placed in a quartz boat, placed in the middle of a tube furnace, heat treated and sulfurized at 750 ° C in an inert atmosphere (nitrogen) for 2 hours, and the obtained product was repeatedly washed with water to remove sodium chloride, and finally a separate chromium trisulfide-porous carbon composite material (Cr2S3-PC) was obtained;

[0090] S4. Dissolve 1 mmol of sodium gluconate in 30 mL of deionized water and stir until completely dissolved; then add 0.33 mmol of zinc sulfate, 2 mmol of thiourea and 30 mmol of sodium chloride in sequence and stir until completely dissolved;

[0091] S5. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0092] S6. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750 ° C for 2 hours in an inert atmosphere (nitrogen), and the obtained product is repeatedly washed with water to remove sodium chloride, and finally a separate zinc sulfide-porous carbon composite material (ZnS-PC) is obtained;

[0093] S7: mixing the chromium trisulfide-porous carbon composite material (Cr2S3-PC) obtained in step S3 and the zinc sulfide-porous carbon composite material (ZnS-PC) obtained in step S6, and grinding them thoroughly to form a uniform composite material.

[0094] The product obtained in step S3 is tested by X-ray diffraction, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS10-0340) of hexagonal phase Cr2S3. Fig. 9 The scanning electron microscope image is shown in Fig.10 , showing that the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology.

[0095] The product obtained in step S6 is subjected to an X-ray diffraction test, and the positions and intensities of the diffraction peaks are consistent with the standard diffraction card (JCPDS 39-1363) of hexagonal ZnS. Fig.11 The scanning electron microscope image is shown in Fig.12 As shown, the product is a three-dimensional porous structure composed of nanosheets with relatively uniform size and morphology.

[0096] The difference between this comparative example and Example 1 is that two types of monometallic sulfide porous carbons are first prepared and then the two are mixed to obtain a composite material.

[0097] Comparative Example 4

[0098] S1. Dissolve 3mmol of sodium gluconate in 30mL of deionized water and stir until completely dissolved; then add 0.66mmol of chromium chloride, 0.33mmol of titanium sulfate, 5mmol of thiourea and 100mmol of sodium chloride in sequence and stir until completely dissolved;

[0099] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0100] S3. The dry powder is placed in a quartz boat, placed in the middle of a tube furnace, and heat treated and sulfurized at 750°C for 2 hours in an inert atmosphere (nitrogen). The obtained product is repeatedly washed with water to remove sodium chloride, and then freeze-dried to obtain the final product.

[0101] The product has been tested by X-ray diffraction. Fig.13 In addition to the diffraction peak of chromium trisulfide, there are also diffraction peaks of titanium oxide and sulfide, indicating that what is obtained is a mixture of chromium trisulfide, titanium oxide and sulfide and carbon material. According to the preparation method of the present invention, chromium and titanium cannot form a bimetallic sulfide with the molecular formula Cr2TiS4.

[0102] Comparative Example 5

[0103] S1. Dissolve 3mmol of sodium gluconate in 30mL of deionized water and stir until completely dissolved; then add 0.66mmol of chromium chloride, 0.33mmol of niobium chloride, 5mmol of thiourea and 100mmol of sodium chloride in sequence and stir until completely dissolved;

[0104] S2. The mixed solution was frozen with liquid nitrogen and then freeze-dried for 12 hours to obtain a dry powder mixture;

[0105] S3. The dry powder is placed in a quartz boat in the middle of a tube furnace, heat treated and sulfurized at 750°C for 2 hours in an inert atmosphere (nitrogen), and the obtained product is repeatedly washed with water to remove sodium chloride, and then freeze-dried to obtain the final product.

[0106] The product has been tested by X-ray diffraction. Fig.14In addition to the diffraction peak of chromium trisulfide, there are also diffraction peaks of niobium oxide and sulfide, indicating that what is obtained is a mixture of chromium trisulfide and niobium oxide and sulfide and carbon material. According to the preparation method of the present invention, chromium and niobium cannot form a bimetallic sulfide with the molecular formula Cr2NbS4.

[0107] Application Examples

[0108] Experimental materials: the composite materials prepared in Examples 1 to 4 and the composite materials prepared in Comparative Examples 1 to 5.

[0109] Experimental methods:

[0110] The composite material prepared in Examples 1 to 4 and Comparative Examples 1 to 5 is used as the electrode active material for electrochemical lithium storage, and is fully mixed with acetylene black and polyvinylidene fluoride in N-methylpyrrolidone solution under stirring to form a uniform slurry, which is evenly coated on the foam copper as the current collector, vacuum dried at 110°C, and then rolled to obtain an electrode; wherein the mass percentage of each component in the electrode is: 70% of the composite material, 15% of acetylene black, and 15% of polyvinylidene fluoride. A lithium sheet is used as the counter electrode, a 1.0 mol / L LiPF6 solution of ethylene carbonate and diethylene carbonate in a volume ratio of 1:1 is used as the electrolyte, and the diaphragm is a polypropylene film (Celguard-2400), and a two-electrode test cell is assembled in a glove box filled with argon. The two-electrode test cell was subjected to constant current charge and discharge test on a program-controlled automatic charge and discharge instrument, using a CT2001A charge and discharge tester from Wuhan Blue Electric Company, with a charge and discharge current density of 0.1 A / g and a voltage of 0.005 to 3.00 V.

[0111] Experimental results:

[0112] The chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) composite material prepared in Example 1 was used as an electrode to obtain a constant current charge-discharge cycle performance of the battery. Fig.15 As shown, it can be seen that the initial capacity of the battery is 1354.4 mAh / g. After 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is still as high as 1066 mAh / g, showing good cycle stability.

[0113] The chromium zinc sulfide-porous carbon (Cr2ZnS4-PC) composite material prepared in Example 2 was used as an electrode to obtain constant current charge and discharge cycle performance of the battery. The initial capacity of the battery was 1152.5 mAh / g, and after 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery was still as high as 833 mAh / g, showing good cycle stability.

[0114] The chromium manganese sulfide-porous carbon (Cr2MnS4-PC) composite material prepared in Example 3 was used as an electrode to obtain a constant current charge-discharge cycle performance of the battery. Fig.16 As shown, it can be seen that the initial capacity of the battery is 1283.5 mAh / g. After 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is still as high as 910 mAh / g, showing good cycle stability.

[0115] The chromium manganese sulfide-porous carbon (Cr2MnS4-PC) composite material prepared in Example 4 was used as an electrode to obtain constant current charge and discharge cycle performance of the battery. The initial capacity of the battery was 1119.3 mAh / g, and after 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery was still as high as 743 mAh / g, showing good cycle stability.

[0116] The chromium zinc sulfide material prepared in Comparative Example 1 was used as an electrode to obtain a battery with a constant current charge and discharge cycle performance as follows: Fig.17 After 100 charge-discharge cycles at a current density of 0.1 A / g, the battery capacity was only 237 mAh / g, showing obvious capacity decay and poor cycle performance. Compared with Example 1, Comparative Example 1 differs only in that no carbon source (sodium gluconate) and pore-forming agent (sodium chloride) are added. After 100 charge-discharge cycles, the battery capacity of the prepared battery decreased by 77.77% compared with Example 1.

[0117] The chromium manganese sulfide material prepared in Comparative Example 2 was used as an electrode to obtain a constant current charge and discharge cycle performance of a battery. Fig.18 After 100 charge-discharge cycles at a current density of 0.1 A / g, the battery capacity was only 205 mAh / g, showing obvious capacity decay and poor cycle performance. The only difference between Comparative Example 2 and Example 3 is that no carbon source (sodium gluconate) and pore-forming agent (sodium chloride) were added. After 100 charge-discharge cycles, the battery capacity decreased by 77.47% compared with Example 3.

[0118] The mixture of Cr2S3-PC and ZnS-PC prepared in Comparative Example 3 was used as an electrode to obtain a constant current charge-discharge cycle performance of the battery. Fig.19 After 80 charge-discharge cycles at a current density of 0.1 A / g, the battery capacity was 639 mAh / g, and showed obvious capacity decay and poor cycle performance.

[0119] The only difference between Comparative Example 4 and Example 1 is that zinc sulfate is replaced by titanium sulfate. The composite material prepared in Comparative Example 4 is used as an electrode to obtain a constant current charge-discharge cycle performance of a battery as shown in FIG. Fig. 20As shown, it can be seen that after 80 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is only 432 mAh / g, and it shows a certain attenuation, and the battery cycle stability is poor.

[0120] The only difference between Comparative Example 5 and Example 1 is that zinc sulfate is replaced by niobium chloride. The composite material prepared in Comparative Example 5 is used as an electrode to obtain a constant current charge and discharge cycle performance of a battery as shown in FIG. Fig.21 As shown, it can be seen that after 70 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is only 513 mAh / g, and it shows obvious attenuation, and the battery cycle stability is poor.

[0121] From the difference in the above experimental results, it can be seen that only the battery prepared by the chromium-based bimetallic sulfide-porous carbon composite material of the present invention has good cycle stability, and it still has excellent battery capacity after 100 charge and discharge cycles.

[0122] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a chromium-based bimetallic sulfide-porous carbon composite material, characterized in that: The steps include: S1. Sodium gluconate, metal salt, sulfur source and pore-forming agent are mixed and dissolved to obtain a mixed solution, and freeze-dried to obtain a mixed dry powder; S2. The dry powder of the mixture prepared in S1 is heat treated and sulfurized at 700 to 900° C. in an inert atmosphere, and the pore-forming agent is removed by post-treatment to obtain a chromium-based bimetallic sulfide-porous carbon composite material; Wherein, the metal salt is a chromium salt and a zinc salt; or a chromium salt and a manganese salt.

2. The preparation method according to claim 1, characterized in that: The molar concentration of sodium gluconate in the mixed solution is 0.01 to 3.0 mol·L -1 .

3. The preparation method according to claim 1, characterized in that: The molar ratio of the metal ions of the metal salt, sodium gluconate, the sulfur source and the pore-forming agent in the mixed solution is 1:1-6:5-10:50-200.

4. The preparation method according to claim 1, characterized in that: In chromium salts and zinc salts, the molar ratio of chromium ion to zinc ion is 1 to 3:1; Or, in the chromium salt and the manganese salt, the molar ratio of chromium ion to manganese ion is 1 to 3:

1.

5. The preparation method according to claim 1, characterized in that: The chromium salt is one or more of chromium chloride, chromium sulfate or chromium nitrate.

6. The preparation method according to claim 1, characterized in that: The zinc salt is one or more of zinc nitrate, zinc acetate or zinc sulfate; Alternatively, the manganese salt is one or more of manganese chloride, manganese acetate or manganese sulfate.

7. The preparation method according to claim 1, characterized in that: The sulfur source is one or both of thiourea and thioacetamide.

8. The preparation method according to claim 1, characterized in that: The heat treatment and vulcanization time is 1 to 4 hours.

9. The chromium-based bimetallic sulfide-porous carbon composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the chromium-based bimetallic sulfide-porous carbon composite material according to claim 9 in lithium-ion batteries.

Citation Information

Cited By

  • Cathode carbon nanosheet of fast-charging sodium-ion battery as well as preparation method and application of cathode carbon nanosheet

    CN120553689A